Career Development in Pediatric Emergency Medicine: What Do We Need?. Issue 9 (28th September 2022) - Chumpitazi, Corrie E.; Allister, Lauren; Cho, Christine; Hoffmann, Jennifer A.; Hsu, Deborah; Iyer, Maya; Mangold, Karen; Marino, Meg; Randell, Kimberly A.; Ponce, Haley; Hariharan, Selena
Abstract : Objectives: The Women in Pediatric Emergency Medicine (PEM) subcommittee of the American Academy of Pediatrics Section on Emergency Medicine identified 2 top priorities for 2021: career development and mentorship/sponsorship. The objective of this study was to catalog and delineate the career development domains for women physicians in PEM. Methods: After a review of the literature to identify the key areas for gaps for women in PEM, we used Q sort methodology to elicit domains for this subcommittee to address by survey of a national sample. Results: One hundred fourteen discrete potential areas of interest for career development were identified by the working group based on salient themes from the literature and personal experiences. Forty-one Women in PEM subcommittee members (27%) completed the survey. The career development topics were sorted into the domains of personal (40.4%; n = 46), administrative (28.1%; n = 32), research (10.5%; n = 12), teaching (10.5%; n = 12), service (7.0%; n = 8), and clinical (3.5%; n = 4). Conclusions: This study demonstrates that the career development needs of women in PEM include a range of personal, teaching, research, administrative, clinical, and service domains. However, more than two-thirds of the career development topics were categorized into just 2 domains, administrative and personal.